Underlying Dimensions of the Five Health-Related Quality-of-Life Measures Used in Utility Assessment: Evidence From the National Health Measurement Study - Cherepanov, Dasha (2010)
BACKGROUND: Preference-weighted health-related quality-of-life (HRQoL) indexes produce a summary score from discrete health states determined by questions falling into several attributes, such as pain and mobility. Values of HRQoL are used alongside other health outcomes to monitor the health of populations. OBJECTIVE: The purpose of this study was to examine among US adults, the underlying factor structure of HRQoL attribute scores across 5 indexes of HRQoL: EuroQol-5 Dimension, Health Utilities Index Mark 2, Health Utilities Index Mark 3, Short Form-6 Dimension, and Quality of Well-Being Scale Self-Administered form. METHODS: The National Health Measurement Study surveyed a nationally representative sample of 3844 noninstitutionalized adults aged 35 to 89 years residing in the continental US. Simultaneous data on all 5 indexes were collected cross-sectionally from June 2005 to August 2006. Exploration of underlying dimensions of HRQoL was done by categorical exploratory factor analysis of HRQoL indexes' attribute scores. Item response theory was applied to explore the amount of information HRQoL attributes contribute to the underlying latent dimensions. RESULTS: Three main dimensions of HRQoL emerged: physical, psychosocial, and pain. Most HRQoL index attributes contributed to the physical or psychosocial dimension. The 3 dimensions were correlated: 0.47 (physical and psychosocial), 0.57 (physical and pain), 0.46 (psychosocial and pain). Some HRQoL index attributes displayed relatively more unique variance: HUI3 hearing, speech, and vision, and some contributed to more than 1 dimension The identified factor structure fit the HRQoL data well (Comparative Fit Index = 0.98, Tucker-Lewis Index = 0.98, and Root Mean Square Error of Approximation = 0.042). CONCLUSIONS: The attributes of 5 commonly used HRQoL indexes share 3 underlying latent dimensions of HRQoL, physical, psychosocial, and pain.